KORELASI KETERAMPILAN MEMBACA PEMAHAMAN DENGAN KETERAMPILAN MENULIS TEKS DESKRIPSI SISWA KELAS VII SMP NEGERI 7 PADANG - Ramizal, Angela; Nursaid, Nursaid; Afnita, Afnita; Syafrina, Dewi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to describe students’ reading comprehension skills, describe students’ descriptive text writing skills, and analyze the correlation between reading comprehension skills and descriptive text writing skills of seventh-grade students at SMP Negeri 7 Padang. This research is a quantitative study using a correlational method. The population consisted of all seventh-grade students, and the sample was selected using purposive sampling. The data were collected through an objective test to measure reading comprehension skills and a performance test to measure descriptive text writing skills. The results showed that students’ reading comprehension skills were in the “more than adequate” category with an average score of 74.50, while their descriptive text writing skills were in the “good” category with an average score of 77.87. The result of the product moment correlation test indicated a significant relationship between reading comprehension skills and descriptive text writing skills, with rcount greater than rtable (0.978 > 0.215). The t-test result also showed that tcount was greater than ttable (42.08 > 1.67), meaning that the hypothesis was accepted. Therefore, the higher the students’ reading comprehension skills, the higher their descriptive text writing skills.